Ammonia volatilization losses from surface-applied urea with urease and nitrification inhibitors - Soares, Johnny Rodrigues; Cantarella, Heitor; Menegale, Marcella Leite de Campos [UNESP] (Elsevier, 2012)
Urease inhibitor (UI) and nitrification inhibitor (NI) have the potential to improve N-use efficiency of applied urea and minimize N losses via gaseous emissions of ammonia (NH 3) to the atmosphere and nitrate (NO3-) leaching into surface and ground water bodies. There is a growing interest in the formulations of coating chemical fertilizers with both UI and NI. However, limited information is available on the combined use of UI and NI applied with urea fertilizer. Therefore the aim of this study was to investigate the effects of treating urea with both UI and NI to minimize NH 3 volatilization. Two experiments were set up in volatilization chambers under controlled conditions to examine this process. In the first experiment, UR was treated with the urease inhibitor NBPT [N-(n-butyl) thiophosphoric acid triamide] at a rate of 1060 mg kg -1 urea and/or with the nitrification inhibitor DCD (dicyandiamide) at rates equivalent to 5 or 10% of the urea N. A randomized experimental design with five treatments and five replicates was used: 1) UR, 2) UR + NBPT, 3) UR + DCD 10%, 4) UR + NBPT + DCD 5%, and 5) UR + NBPT + DCD 10%. The fertilizer treatments were applied to the surface of an acidic Red Latosol soil moistened to 60% of the maximum water retention and placed inside volatilization chambers. Controls chambers were added to allow for NH 3 volatilized from unfertilized soil or contained in the air that swept over the soil surface. The second experiment had an additional treatment with surface-applied DCD. The chambers were glass vessels (1.5 L) fit with air inlet and outlet tubings to allow air to pass over the soil. Ammonia volatilized was swept and carried to a flask containing a boric acid solution to trap the gas and then measured daily by titration with a standardized H 2SO 4 solution. Continuous measurements were recorded for 19 and 23 days for the first and second experiment, respectively. The soil samples were then analyzed for UR-, NH4+-, and NO3--N. Losses of NH 3 by volatilization with unamended UR ranged from 28 to 37% of the applied N, with peak of losses observed the third day after fertilization. NBPT delayed the peak of NH 3 losses due to urease inhibition and reduced NH 3 volatilization between 54 and 78% when compared with untreated UR. Up to 10 days after the fertilizer application, NH 3 losses had not been affected by DCD in the UR or the UR + NBPT treatments; thereafter, NH 3 volatilization tended to decrease, but not when DCD was present. As a consequence, the addition of DCD caused a 5-16% increase in NH 3 volatilization losses of the fertilizer N applied as UR from both the UR and the UR + NBPT treatments. Because the effectiveness of NBPT to inhibit soil urease activity was strong only in the first week, it could be concluded that DCD did not affect the action of NBPT but rather, enhanced volatilization losses by maintaining higher soil NH4+ concentration and pH for a longer time. Depending on the combination of factors influencing NH 3 volatilization, DCD could even offset the beneficial effect of NBPT in reducing NH 3 volatilization losses. © 2012 Elsevier Ltd.
Keywords: Ammonia volatilization; DCD; NBPT; Nitrification inhibitor; Stabilized fertilizer; Urea; Urease inhibitor; Urease inhibitors; Ammonia; Denitrification; Experiments; Fertilizers; Groundwater; Inorganic acids; Leaching; Nitrification; Oxidation; pH effects; Soils; Surface treatment; Urea fertilizers; Metabolism; ammonia; coating; enzyme activity; fertilizer application; inhibitor; nitrification; nutrient use efficiency; soil chemistry; soil surface; urea; volatilization